2016
DOI: 10.3847/0067-0049/223/2/19
|View full text |Cite
|
Sign up to set email alerts
|

THE NEW HORIZONS SOLAR WIND AROUND PLUTO (SWAP) OBSERVATIONS OF THE SOLAR WIND FROM 11–33 au

Abstract: The Solar Wind Around Pluto (SWAP) instrument on National Aeronautics and Space Administrationʼs New Horizons Pluto mission has collected solar wind observations en route from Earth to Pluto, and these observations continue beyond Pluto. Few missions have explored the solar wind in the outer heliosphere making this dataset a critical addition to the field. We created a forward model of SWAP count rates, which includes a comprehensive instrument response function based on laboratory and flight calibrations. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…Finally, we validated these results using an adapted version of the SWAP analytic model [Elliott et al, 2016], which assumes a drifting Maxwellian. With that, we found very similar results with somewhat lower densities and temperatures, likely because a Maxwellian does not capture the broader, non-Maxwellian wings of the observed distributions.…”
Section: 1002/2016ja022599mentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, we validated these results using an adapted version of the SWAP analytic model [Elliott et al, 2016], which assumes a drifting Maxwellian. With that, we found very similar results with somewhat lower densities and temperatures, likely because a Maxwellian does not capture the broader, non-Maxwellian wings of the observed distributions.…”
Section: 1002/2016ja022599mentioning
confidence: 91%
“…These included SWAP observations of the pristine solar wind before and after the flyby, which indicated that the solar wind was quite steady with approximate inferred proton moments [Elliott et al, 2016] at the time of the flyby of v p~4 03 km s À1 , n p~0 .025 cm…”
Section: Introductionmentioning
confidence: 99%
“…Our first step was to estimate the time interval during which the ICME would reach New Horizons. We assumed that the ICME cannot travel faster than the mean velocity between Rosetta and Cassini (560 km/s, see Table ) and also cannot travel slower than the lowest solar wind speed (~400 km/s) measured by New Horizons in early 2015 (see Figure , which shows solar wind parameters from the Solar Wind Around Pluto (SWAP) instrument [ Elliott et al ., ] including the energy per charge count rate spectrogram and the solar wind speed, density, temperature, and dynamic pressure for the period 31 December 2014 to 15 March 2015). This leads to an interval of 18 January to 14 February 2015 (day of year (DOY) 18–45) in which to search for evidence of the ICME at New Horizons.…”
Section: Propagation Of the Interplanetary Coronal Mass Ejection: Fromentioning
confidence: 99%
“…The radial velocity varies steeply between 300 and 600 km s −1 at 1 AU, but the fluctuations at both small and large scales are considerably reduced with distance, in agreement with SWAP data . While stream interaction between parcels of wind with different speed is responsible for gradually removing small and mid-size structures (Gazis et al 1995;Richardson et al 1996Richardson et al , 2002Elliott et al 2016), large scale fluctuations are affected by changes related to solar cycle. For example, a number of persistent, low-latitude coronal holes during the SC 23 minimum were associated with recurring fast wind streams of ∼600 km s −1 at 1 AU (Abramenko et al 2010), but such fast streams appear less frequently in OMNI data after 2009 in SC 24.…”
Section: Comparison With Nh Swap Datamentioning
confidence: 99%
“…4.-Model |B|, radial velocity, and number density are compared to the daily averaged NH-SWAP data. Adapted from Elliott et al (2016) with permission of the AAS. …”
Section: Comparison With Nh Swap Datamentioning
confidence: 99%